Severe clozapine poisoning – case presentation - Majewska, Magdalena; Szponar, Jarosław (Current Problems of Psychiatry, 2011)
Clozapine is an antipsychotic drug, which belongs to the group of atypical antipsychotic agents for the treatment of schizophrenia. Clozapine is a very effective medicine, but because of the possibility of inducing severe side effects, clozapine should be recommended only for patients who do not respond to other treatments or do not tolerate other drugs. Case presentation: a young 29-year-old man was hospitalized in the Regional Centre of Clinical Toxicology in Lublin, because of suicidal overdose of dozens of clozapine pills. The patient was taking clozapine due to paranoid schizophrenia. At the time of admission to hospital the patient was in severe general condition and there was no logical contact with him. In the laboratory test we observed severe features of lactic acidosis, which could be typical for clozapine poisoning. In addition the patient developed acute respiratory failure and rhabdomyolysis. For the next 6 days, thepatient required intensive treatment and care, including periodic respiratory therapy. The patient was discharged from the hospital in good general condition after 13 days of treatment and he was referred to Neuropsychiatric Hospital in Lublin. The patient was diagnosed in the course of clozapine poisoning with: toxic coma, lactic acidosis, acute respiratory failure, pneumonia and rhabdomyolysis.